Assessment of tripartite headache in a case of depression with partial empty sella syndrome - Sutar, Roshan F. (Indian J Psychiatry, 2020)
Headache is multifactorial and can be classified as primary and secondary. It is a common notion for a treating clinician to oversee other causes of headache once the diagnosis of one type of headache has been made. Association of multiple types of headache together in a single patient is not uncommon, but often missed due to busy outpatient setting. The repeated visits of such patient for the treatment of headache can increase the burden on health-care utilization, especially in lower-middle-income countries like India. Patience, documentations, openness to dual pathology, and educating patient play an instrumental role in the assessment of headache.